Incorporação orgânica da educação a distância nas universidades públicas - Veloso, Braian Garrito (Universidade Federal de São Carlos, 2022)
Distance Education (DE) has been growing dramatically, being also driven by the experiences lived during the pandemic period, namely in what is conventionally called emergency remote teaching - or similar nomenclatures. In Brazilian public universities, the modality has grown predominantly through the Universidade Aberta do Brasil (UAB) System. That said, the general objective of this thesis was to analyze how public universities (state and federal), operating within the UAB System, have organized themselves in order to organically incorporate DE into their institutional practices. As for the methodology, methodological triangulation was used in the light of qualitative and quantitative approaches. In addition, the investigation had, as an epistemological matrix, the Weberian comprehensive sociology. Regarding the methodological procedures, the research was divided into two main moments, the first being carried out in Brazil and the second in Portugal. The first moment had the following steps: survey and bibliographic study; document analysis; Delphi technique; virtual questionnaire; focus groups and; semi-structured interview. The second moment, carried out in the delegation of the city of Porto of the Universidade Aberta de Portugal, included: bibliographic study and document analyses; on-site visits; semi-structured interview and; monitoring of training activities in the Azores. As a result, the thesis shows that the UAB System generated a standardization in distance courses, despite some specificities that concern the proposals of each institution. As a rule, constituting DE management centers to centralize practices in the modality. Teaching, on the other hand, relies on the division of labor and receiving scholarships to work. In learning, it is clear that the UAB System has a central-pole model, in addition to the use of the Moodle virtual environment. Thinking about the institutionalization process, some important advances were made, such as the inclusion of the modality in normative documents, constitution of a management center with autonomy in its functions, students with some opportunities and rights equivalent to those of face-to-face education, etc. But these steps were not climbed without challenges. The word “struggle” frequently appears in the speeches of the subjects participating in the study. Starting from this, we arrive at the interpretation that understands the phenomenon of institutionalization as essentially dialectical, that is, involved in institutional conflicts that move the process. In order to advance in the incorporation of DE, we argue that it is necessary to overcome what we call, in the thesis, the institutionalization of precariousness. Therefore, through the speeches and experiences of the research participants, we proposed reflections on strategies aimed at organic incorporation. It becomes important, therefore, to act in the light of the dimensions: bureaucracy, confluence between modalities, experience and organizational culture. At the end of the thesis, we present the data collected at the Open University of Portugal, defining the public DE model in that country and comparing it, as much as possible, with the Brazilian reality. We identified some approximations, but also distances. When it comes to institutionalization, the main difference concerns the eminently endogenous character, in Brazil, and exogenous, in Portugal. To end the analysis, we present hybrid education as a historical trend that will be – and is being – built at a junction between subjective and material aspects in both countries.
Organic incorporation of distance education in public universities
Keywords: Educação a distância; Institucionalização; Incorporação orgânica; Sistema Universidade Aberta do Brasil; Distance education; Institutionalization; Organic incorporation; Universidade Aberta do Brasil System; CIENCIAS HUMANAS::EDUCACAO